2013
DOI: 10.1186/1471-2369-14-144
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TWEAK independently predicts atherosclerosis in renal transplant patients

Abstract: BackgroundCardiovascular risk is increased in the early stages of chronic kidney disease (CKD) and also found to be ongoing in renal transplant (Rtx) patients. As a sign of atherosclerosis, increased carotid intima-media thickness (CIMT) has been widely accepted as a strong predictor of cardiovascular disease (CVD) and mortality in CKD patients. A novel markers, soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) and neutrophil-to-lymphocyte ratio (NLR) were introduced as potential markers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…sTWEAK was negatively and independently associated with c-IMT in agreement with previous studies on asymptomatic subjects (13) and patients with CKD not on dialysis (28,29). However, positive association between sTWEAK and c-IMT has been reported in patients with transplants and CKD (30), which could be because of the presence of special therapy regimens used in patients with transplants and CKD.…”
Section: Discussionmentioning
confidence: 93%
“…sTWEAK was negatively and independently associated with c-IMT in agreement with previous studies on asymptomatic subjects (13) and patients with CKD not on dialysis (28,29). However, positive association between sTWEAK and c-IMT has been reported in patients with transplants and CKD (30), which could be because of the presence of special therapy regimens used in patients with transplants and CKD.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, c-IMT was inversely associated to sTWEAK in asymptomatic subjects [11] and in patients with chronic kidney disease [17e19]. However, this association has not been confirmed in other patient populations and, indeed, positive correlation between sTWEAK and c-IMT has been reported [20,21]. On the other hand, it has been reported that sTWEAK concentrations are negatively associated with flowmediated dilation (FMD) in patients with CKD, persisting after adjustment for factors related to FMD [17,22,23].…”
Section: Introductionmentioning
confidence: 92%
“…Numerous low-powered cross-sectional ultrasound studies of carotid arteries have been performed in patients with renal transplants (28)(29)(30)(31)(32). The vast majority of these studies considered isolated biomarkers (mainly biomarkers of inflammation) (29,31,32) or just a limited set of purported risk factors. Longitudinal studies have several advantages over cross-sectional studies for exploring causation.…”
Section: Discussionmentioning
confidence: 99%
“…Among nonclassic risk factors, CRP (9) and biomarkers of CKD-MBD (10) undergo dramatic changes after transplantation, and FGF23 and 1,25(OH) 2 vitamin levels approach the normal range in most patients, whereas serum PTH often remains mildly to moderately elevated (27). Numerous low-powered cross-sectional ultrasound studies of carotid arteries have been performed in patients with renal transplants (28)(29)(30)(31)(32). The vast majority of these studies considered isolated biomarkers (mainly biomarkers of inflammation) (29,31,32) or just a limited set of purported risk factors.…”
Section: Discussionmentioning
confidence: 99%